Legal Protection Workers in The Agreement in Photography Studio WHC Purwokerto - Dwimo Gogy Prabowo (Authentica, 2018)
Labor has a very important role in national development. Labor (man power) are residents who have or are working, looking for work and carry out other activities such as schools and care of the household. Thus the workers have their own rights and obligations that must be fulfilled, with the rules governing the employment and the employer to ensure that workers in the work. In addition, the worker and the employer must also have a working agreement that binds them. The basic working agreement should also contain provisions relating to the employment relationship, the rights and obligations of workers and the rights and obligations of employers. In the pre-study in WHC Studio Purwokerto I get the primary data that employees working agreement with his employer orally or in writing. In the execution of the workers in the WHC photography studio doing a lot of work outside of his agreement. Viewed from pre-study in WHC Studio orally there is agreement that ultimately there is no legal certainty in work and in remuneration, and therefore need further study.Keywords: legal protection; the Agreement; Employment